Kukoamine B regulates pyroptosis mediated by NLRP3/Caspase-1/GSDMD pathway to alleviate lipopolysaccharide-induced macrophage inflammation - NING Pu; KE Rui; HE Ping; YANG Shuanying (Guangxi Yike Daxue xuebao)
Objective To investigate the regulatory effect of kukoamine B (KB) on the nucleotide-binding oligomerization domain-like receptor protein 3 (NLRP3)/Caspase-1/gasdermin D (GSDMD) pyroptosis pathway in human monocytic leukemia THP-1 cells induced by lipopolysaccharide (LPS). Methods THP-1 cells were induced into macrophage by 100 ng/mL phorbol 12-myristate 13-acetate (PMA) for 24 h. The cell counting kit-8 (CCK-8) assay was used to assess the effect of KB on cell viability, and the appropriate concentrations were determined for subsequent experiments. The inflammation injury model of macrophage (LPS group) was established by LPS combined with adenosine triphosphate (ATP). The cells were treated with different concentrations of KB and NLRP3 inflammasome inhibitor MCC950. Reverse transcription-quantitative polymerase chain reaction (RT-qPCR) was employed to detect the mRNA expression of NLRP3, Caspase-1, apoptosis-related spot-like protein (ASC), interleukin (IL)-1β, GSDMD and high mobility group protein B-1 (HMGB-1) in each group. Western blotting was used to detect the expression of the inflammasome components and pyroptosis-associated proteins. The IL-1β level in supernatant was determined via enzyme-linked immunosorbent assay (ELISA), the release of lactate dehydrogenase (LDH) in the cell supernatant was assessed, and the Annexin-V-PE/7-aminoactinomycin (7-AAD) staining was utilized to detect apoptosis. Results The concentrations of KB ranging from 12.5 μmol/L to 400 μmol/L had no significant effect on the viability of THP-1 cells. In comparison to the control group (untreated cells), the expression of NLRP3, Caspase-1, IL-1β, GSDMD and HMGB-1 mRNA was up-regulated in the LPS group. After MCC950 or KB treatment, the above changes were significantly reversed (P＜0.05). The protein expression of NLRP3, Caspase-1, Cleaved caspase-1, GSDMD, GSDMD-NT, and HMGB1 in the LPS group were higher than those in the control group, and the above protein expression was down-regulated after MCC950 or KB treatment. The secretion of IL-1β and LDH release in cell culture supernatant were decreased (both P＜0.05), and the apoptosis was reduced. Conclusion KB can alleviate LPS-induced inflammation in THP-1 cells by inhibiting pyroptosis mediated by the NLRP3/Caspase-1/GSDMD pathway.